Income and Wealth Shocks and Expectations during the COVID-19 Pandemic - Tobin Hanspal; Annika Weber; Johannes Wohlfart (Center for Economic Studies and ifo Institute (CESifo), 2020)
In early April 2020 we conducted a survey on a representative sample of more than 8,000 US households to study the effect of the coronavirus crisis on household income and retirement wealth, households' expectations about the recovery, and the impact of the shock on individuals' economic choices. Wealth shocks are large across the population, but more pronounced for middle-age households and those higher in the wealth and income distributions. This contrasts with income shocks, which are stronger for younger households and those in lower income and wealth quintiles. Expectations about household spending are affected by income shocks, but not by financial wealth shocks. Both wealth and income shocks are associated with upward adjustments in expectations about household debt, desired working hours, and retirement age. Finally, respondents expect the recovery of the stock market to occur more quickly than for previous stock market crashes and beliefs on the duration are strongly correlated with expectations about own wealth, debt, and labor market activity.
Keywords: D14; D31; D83; D84; D91; 330; coronavirus; wealth shocks; income shocks; expectations; inequality